Inclusión educativa y su influencia en el desarrollo socio afectivo en los niños del subnivel 2 de la Unidad Educativa Francisco Huerta Rendón - Medrano Suárez, Joicy Nayely (2023)
Within this research project we will try to demonstrate the influence that educational inclusion has on the socio-affective development of infants, since it seeks to maintain a balance between the educational relationships that can be created within the classroom. For this reason, it was evident that, in the “Francisco Huerta Rendón” Educational Unit, highlighting sublevel 2, parents, as well as teachers, do not have knowledge about how important the development of good educational inclusion is for the optimal daily development of infants. Therefore, it is proposed that training be given for teachers and, in turn, for parents, since this way they will know how to help them in their academic development together with other children, because this is where children will create their own knowledge and develop their emotions. It should be noted that, within this research work, descriptive, documentary, exploratory and field research will be used, in addition to a mixed research approach, which will give us a deeper perspective of the problem. Finally, the mixed research design and the deductive and inductive methods are present. That is why, as a final product of this research carried out at sublevel 2 of said aforementioned institution, the lack of a sense of inclusion in the classroom on the part of the children was verified, which does not allow their socio-affective development. Therefore, activities are needed that contribute to this development, since it will be a fundamental part of the child's future life.